Analysis of H/V Ratio Curve to Estimate Seismic Hazard Vulnerability in Lombok Island, West Nusa Tenggara, Indonesia - Muhammad Randy Caesario Harsuko; Zulfakriza Z.; Andri Dian Nugraha; Muzli Muzli; David Prambudi Sahara; Nanang T Puspito; Yayan M Husni; Billy S Prabowo; Achmad Fajar Narotama Sarjan (Himpunan Ahli Geofisika Indonesia (HAGI), 2020)
In 2018, Lombok Island was hit by a series of destructive earthquakes. According to Indonesian Meteo- rological, Climatological, and Geophysical Agency data, about 1,973 felt earthquakes (M > 3) which shaken Lombok were recorded during August 2018 with three earthquakes with the largest magnitude of 6.9 Mw, 6.8 Mw, and 6.2 Mw. National Board for Disaster Management reported about 555 deaths, 1,833 people injured, and 186,010 houses damaged as a result of Lombok earthquake on August 5th, 2018. A number of seismometers were placed on Lombok Island from August 3rd, 2018 to October 19th, 2018 to monitor the aftershock events. There are 17 stations that record seismicity in Lombok consisting of 10 broadband sensors and 7 short period sensors. In this study, we used the Horizontal-to-Vertical Spectral Ratio (HVSR) method to analyze the risk of earthquake in the Lombok region. The basic concept of this method is to do a comparison between the horizontal component spectrum and the vertical component spectrum of a wave, where theoretically the particle movement of the horizontal component is greater than the particle movement of the vertical component on soft ground, whereas on the hard ground both components (horizontal and vertical) will be similar. H/V curve obtained from earthquake record- ings (Earthquake Horizontal-to-Vertical Ratio/EHVR) and H/V curve obtained from microtremor recordings (Microtremor Horizontal-to-Vertical Ratio/MHVR) shows good agreement and high correlation. Empirical correction of EMR (Earthquake-to-Microtremor Ratio) managed to decrease the difference of estimation of predominant frequency and amplification factor between EHVR and MHVR. Predominant frequency, amplification, and seismic vulnerability map agree with the geological condition of Lombok Island, where high value of amplification and seismic vulnerability was found on soft and thick ground. This study conclude that the maximum ground acceleration and the construction of the building should also considered when one wants to investigate the effect of an earthquake to the damage occurred, beside the site effects.